HUBUNGAN INDEKS MASSA TUBUH (IMT) DENGAN RISIKO INFERTILITAS PADA WANITA USIA SUBUR DI KLINIK FERTILITAS MERCY PEKANBARU - Donna Octavia Cendana Putri; Rifa Yanti; Meirita Herawati; Yesi Septina Wati (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2026)
Infertility is a reproductive health problem that impacts the quality of life of couples, while obesity is known to be a significant risk factor that can affect fertility through hormonal disorders, insulin resistance, and ovulation quality. This study aims to analyze the relationship between obesity and infertility in women of childbearing age at the Mercy Fertility Clinic in Pekanbaru. This study used a quantitative method with a cross-sectional analytical design, conducted in January–August 2025. The study population was all 117 women of childbearing age who visited the clinic in 2024. A sample of 91 respondents was selected using a purposive sampling technique based on inclusion criteria, namely women aged 20–45 years who were diagnosed with primary infertility and were willing to be respondents. Primary data were obtained through BMI measurements and filling out questionnaires, while secondary data came from clinic records. Data processing was carried out through editing, coding, entry, and cleaning stages, then analyzed univariately and bivariately with the Chi-Square test (α = 0.05). The results showed that 69.2% of respondents were obese and 69% experienced infertility. There was a significant association between BMI and infertility (p = 0.000). It is recommended that the Mercy Pekanbaru Fertility Clinic provide weight management services through nutritional counseling, healthy diet programs, and BMI monitoring to improve the success of pregnancy programs in women of childbearing age. Keywords: Body Mass Index (BMI), Obesity, Infertility, Women of Reproductive Age